2019
DOI: 10.1177/0018726719876687
|View full text |Cite
|
Sign up to set email alerts
|

Ethics, politics and embodied imagination in crafting scientific knowledge

Abstract: This article explores ‘research-as-craft’ as a sensitizing concept for disclosing the presence of ethics and politics, as well as embodiment and imagination, in the doing and representation of scientific activity. Routinely unnoticed, marginalized or suppressed in methodology sections of articles and methodology textbooks, research-as-craft gestures towards messy, tacit, uncertain, yet rarely thematized, practices that are central to getting science done. To acknowledge and address the significance of research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 102 publications
(166 reference statements)
0
61
0
Order By: Relevance
“…The same developments can be observed in education, particularly management education and learning, where the transmission of knowledge has increasingly become attuned to the needs of business and society as a form of ‘mercantilization of knowledge’ (Lyotard, 1984: 51). Moreover, taking a research-as-craft gesture here, we try to use disruptive reflexivity in pinpointing the attempted separation of ethics and politics from knowledge production, which is endeavouring to seek closure, marginalising the tacit, embodied, enacted and sensuous knowledge of the powerless (Bell and Willmott, 2019). To reinforce this point, Kothiyal et al (2018) showed how globalisation, combined with the historical legacy of colonialism, the dominance of the English language and a pressure to conform to research norms set by globally ranked journals in particular, has increased the precarious position of scholars in emerging markets.…”
Section: ‘Taking Back Freedom’ From the Performative University Of ‘Tmentioning
confidence: 99%
“…The same developments can be observed in education, particularly management education and learning, where the transmission of knowledge has increasingly become attuned to the needs of business and society as a form of ‘mercantilization of knowledge’ (Lyotard, 1984: 51). Moreover, taking a research-as-craft gesture here, we try to use disruptive reflexivity in pinpointing the attempted separation of ethics and politics from knowledge production, which is endeavouring to seek closure, marginalising the tacit, embodied, enacted and sensuous knowledge of the powerless (Bell and Willmott, 2019). To reinforce this point, Kothiyal et al (2018) showed how globalisation, combined with the historical legacy of colonialism, the dominance of the English language and a pressure to conform to research norms set by globally ranked journals in particular, has increased the precarious position of scholars in emerging markets.…”
Section: ‘Taking Back Freedom’ From the Performative University Of ‘Tmentioning
confidence: 99%
“…The view that intuition is involved in organizational research is part of at least two ongoing theoretical conversations. First, the claim to report intuition is linked to Bell andWillmott's (2020: 1380) perspective that research should be seen as 'more embodied, less certain, less cognitive, and more emotionally demanding', and method sections should account for those features. Bell and Willmott's article is in the tradition of earlier arguments on reflexivity in research that have questioned the ideal of 'objectivity' and challenged the idea of an independent, external reality (e.g.…”
Section: The Role Of Intuition In Organizational Researchmentioning
confidence: 99%
“…Behfar and Okhuysen, 2018;Bell and Willmott, 2020;Klag and Langley, 2013;Locke et al, 2008). As one crucial aspect, there has been an importance attached to acknowledging the role of intuition-'direct knowing without any use of conscious reasoning' (Sinclair, 2010: 378)-in the 'craft' of research (Bell and Willmott, 2020;Dörfler and Eden, 2019). However, reporting the use of intuition can be difficult for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…We propose a weaving metaphor 2 to show that discursive practices can be woven together in ways that generate conversations in which participants are neither domineering nor dominated, but are welcoming, inclusive and respectful of each other; where they listen, while recognizing there will be limits on what they are able to hear; and where they are both critical and appreciative of the past at the same time as being receptive to learning about open-ended, unknown futures (also see Hamann et al, 2020; Spiller, Wolfgramm, Henry, & Pouwhare, 2020). Our invocation of a craft metaphor is intended to acknowledge the complex and paradoxical nature of organizational theorizing, and speak to its ‘embodied, imaginative, ethical and political nature’ (Bell & Willmott, 2019, p. 2). It is not, then, a template or a list of particular practices but, rather, is intended to suggest ‘know-how’ that may help others weave new patterns in different ways.…”
Section: Weaving a Way Forwardmentioning
confidence: 99%